El Von Bertalanffy and Mortality from Fish Kurau (Polynemustaenitatus) of The Catch Fisherman in Waters Bunyu - Gazali Salim; Pius Bae Kelen (INSIST, 2018)
The aim of the research are analyzing the growth model using Von Bertalanffy and mortality in Polynemus taeniatus.  Research methods a descriptive kuantitatif by using the case study. Determining the location of sampling are purposive sampling, by following fishing boats Drift Gill Net. Sampling funded every two weeks once upon a huge tide. Data collection techniques using survey. Data retrieval in the form of total length and total weight. The samples from 4 (times) for 3 months. Each sample taking having vulnerable time between 2-5 day in bunyu waters. Research results use the model von bertalanffy obtained maximum length fish kurau (p.taeniatus) is 156,794 cm in 349 days. Value K of 0.0364 cm.  Value To of -1,2819 cm. The results of data processing of fish catch kurau (P.taeniatus) obtained by mortalitas natural 0,435; mortalitas total of 1.121; mortalitas arrest of 0,6859; the exploitation of fish kurau 0,61.